Faktografinis informavimas bibliotekoje - Masiokas, Mykolas (Knygotyra, 1986)
The reference literature and factographic reference lists have very old traditions in the libraries. The theoretical development of factography and the increased amount of factographic documents put the library against the new problems. The conception of factographic information service in the library is formulated in the article.